2019
DOI: 10.3892/mmr.2019.10877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SKF‑96365 on cardiomyocyte hypertrophy induced by angiotensin II

Abstract: angiotensin ii (ang ii) is an important bioactive peptide in the renin-angiotensin system, and it can contribute to cell proliferation and cardiac hypertrophy. dysfunctions in transient receptor potential canonical (TrPc) channels are involved in many types of cardiovascular diseases. The aim of the present study was to investigate the role of the TrPc channel inhibitor SKF-96365 in cardiomyocyte hypertrophy induced by ang ii and the potential mechanisms of SKF-96365. H9c2 cells were treated with different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Levels of Brn-3b mRNA and related proteins are increased in Ang II treated mouse hearts and foetal heart-derived H9c2 cells or primary cultures of neonatal rat ventricular myocytes with varied hypertrophic alterations. Alternate signaling pathways involved in activation of Brn-3b promoter include p42/p44 MAPK/ERK1/2 or calcineurin pathways ( Mele et al, 2019 ; Cheng et al, 2020 ). Cardiac fibrosis is induced by the pro (renin) receptor, which could be more worsened by the involvement PRR-ERK1/2-NOX4 pathway and ROS during the development of alcoholic cardiomyopathy ( Cao et al, 2019 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…Levels of Brn-3b mRNA and related proteins are increased in Ang II treated mouse hearts and foetal heart-derived H9c2 cells or primary cultures of neonatal rat ventricular myocytes with varied hypertrophic alterations. Alternate signaling pathways involved in activation of Brn-3b promoter include p42/p44 MAPK/ERK1/2 or calcineurin pathways ( Mele et al, 2019 ; Cheng et al, 2020 ). Cardiac fibrosis is induced by the pro (renin) receptor, which could be more worsened by the involvement PRR-ERK1/2-NOX4 pathway and ROS during the development of alcoholic cardiomyopathy ( Cao et al, 2019 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…In the heart, the phenomenon of hypertrophy results from increased cardiomyocyte size, which is secondary to pressure or mechanical overload. Several studies provided evidence that TRPC channels may contribute to the development of cardiac hypertrophy [ 129 , 130 , 131 , 132 , 133 ]. Hearts from hypertrophic patients had higher TRPC1 expression [ 134 ], and the cardiomyocytes from hypertrophic mouse models showed upregulated TRPC1/TRPC4 function [ 135 ].…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…These inhibitors blocked pathological hypertrophic signaling in adult cardiac myocytes [ 130 ]. SK&F-96365, an unspecific inhibitor of receptor-operated, Cav, and TRPC channels, also attenuated cardiomyocyte hypertrophy induced by Ang II [ 133 ]. Interestingly, it was demonstrated that the protection conferred by TRPC3 deletion is not only due to the reduction of Ca 2+ influx mediated by TRPC3, but also through the modulation of Ca V 1.2 expression, which is downregulated in TRPC3 KO mice and leads to reduced response in phenylephrine-induced cardiac hypertrophy [ 131 ].…”
Section: Physiological and Pathological Functions Of Trpcs Revealementioning
confidence: 99%
“…10 1-[2-(4-methoxyphenyl)-2-[3-(4-methoxyphenyl) propoxy]ethyl-1H-imidazole (SKF-96365) is a small molecule compound acting as a non-selective inhibitor of TRP channels, SOCE and voltagegated Ca 2+ channels, and SKF-96365 has been proved to suppress cellular Ca 2+ influx via inhibiting these Ca 2+ channels. [11][12][13] There is ample evidence that SKF-96365 is widely used to study the function of TRPC channels. [12][13][14][15][16][17] Previous reports indicate that SKF 96365 could suppress cardiomyocyte hypertrophy, and inhibit spontaneous nociception and pain hypersensitivity induced by melittin via inactivating TRPC channels and Ca 2+ influx.…”
Section: Introductionmentioning
confidence: 99%
“… 12 17 Previous reports indicate that SKF 96365 could suppress cardiomyocyte hypertrophy, and inhibit spontaneous nociception and pain hypersensitivity induced by melittin via inactivating TRPC channels and Ca 2+ influx. 12 , 18 In cultured NECs, TRPC6, STIM1, Orai1, Ca 2+ MFI levels, and inflammatory mediators were upregulated by lipopolysaccharide (LPS) and 1-oleoyl-2-acetyl-glycerol (OAG, diacylglycerol (DAG) analog, TRPC6 activator), but were inhibited by SKF-96365. 10 In addition, 2-aminoethoxydiphenyl borate (2-APB) is a chemical which could inhibit SOCE and TRP channels, 19 , 20 and one previous report has indicated that 2-APB administration intranasally could reduce numbers of sneezing, nasal rubbing, and eosinophils in murine AR.…”
Section: Introductionmentioning
confidence: 99%